A study of quality of concrete at site construction and working culture during concreting - Khairil Anis, Suhaimi (2015)
Quality of concrete produced not only assessed from two different construction sites, but can also be distinguished only in one construction site only with a cluster of different mixes. In fact, the quality of concrete is highly dependent on the quality of and quantity of the mixture is used, the quality of work mixing and pouring concrete, quality control and supervision as well as environmental factors. Lately, concrete qualities often disputed. Especially by the customer, especially involving construction projects. All 6 constructions site are selected to done this study. All data will be collected by questionnaire and my own observation at construction site. All data collection will be analysing into IBM SPSS STATISTICS version 20 to show the results. The results shows that the awareness of important of quality concrete still in weakness level. Although all correspondent known very well about the quality of concrete but, they not do it in right way such as storing a materials and culture during concreting. Therefore, JKR or responsible parties need to rise up a level of supervision at construction site to rise up level of quality concrete.